Circular RNA circ-BNC2 (hsa_circ_0008732) inhibits the progression of ovarian cancer through microRNA-223-3p/ FBXW7 axis - Ting Liu; Li Yuan; Xiaofeng Zou (BMC, 2022)
Abstract Background Circular RNAs (circRNAs) are reported to be key regulators in the progression of human cancers. This work focuses on the function and molecular mechanism of circRNA-BNC2 (circ-BNC2) (also known as hsa_circ_0008732) in ovarian cancer (OC). Methods Quantitative real-time polymerase chain reaction (qRT-PCR) was conducted to detect circ-BNC2, microRNA-223-3p (miR-223-3p) and F-box and WD repeat domain containing 7 (FBXW7) mRNA expressions in OC tissues and cells. Besides, cell counting kit 8 (CCK-8), transwell assay and cell cycle assays were executed to assess the proliferative, migrative, invasive abilities, and cell cycle progression of OC cells, respectively. Dual-luciferase reporter gene assay and RNA pull-down assay were used to validate the targeting relationships between miR-223-3p and circ-BNC2 or FBXW7. Western blot was adopted to determine FBXW7 protein levels in OC cells. Results Circ-BNC2 expression was downregulated in OC tissues and cell lines, which was associated with higher FIGO stage and lymph node metastasis of OC patients. Circ-BNC2 overexpression repressed the proliferation, migration, invasion of OC cells and induced cell cycle arrest, while silencing circ-BNC2 worked oppositely. Mechanistically, circ-BNC2 could upregulate FBXW7 expression in OC cells via sponging miR-223-3p. Conclusion Circ-BNC2 suppresses the progression of OC via regulating miR-223-3p / FBXW7 axis. Our findings provided potential biomarker for OC therapy.